Innovativeness of the Economy and Innovation Policy of Regions - Szostak, Ewa (Innowacyjność gospodarki a polityka innowacyjna regionów, 2010)
National innovation policy is implemented at two levels: central and regional one. For self-government authorities this is a relatively new area of activities. The aim of the article is to present the basis and to reveal the importance of regional innovation policy in increasing the economy competitiveness.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 111, s. 752-761
Keywords: regional innovation policy; competitiveness; innovation